Nutrient Fluxes between Sediment and Water in the Shatt Al-Arab Estuary, Northwestern Arabian Gulf - Fakher, Noor (Iraqi Journal of Aquaculture, 2026)
Nutrient exchange occurred at four stations located downstream of the Shatt Al-Arab River and in the northwestern Arabian Gulf. The stations (Al-Ashar, Abu Flous, Al-Seeba, and Al-Faw) were studied over four seasons (autumn, winter, spring, and summer) of 2024–2025. These samples were then analyzed for total nitrogen (TN), total phosphorus (TP), nitrite (NO₂), nitrate (NO₃), and (PO₄). The seasonal water results will show significant spatial and temporal changes in nutrient levels driven by seasonal river discharge, seawater intrusion, and human activities such as farming and urban runoff. The concentrations of TN, TP, NO₂, NO₃, and PO₄ are high at the downstream stations (24.08 mg/l – 0.281 mg/l – 0.9322 mg/l – 0.009 mg/l ), whereas low readings were recorded at the upstream stations (1.12 mg/l – 0.0042 mg/l – 0.007116 mg/l – 0.0143 mg/l – 0.001 mg/l ). The sediment samples yielded results that varied widely. They gave higher concentrations than water (16.8 mg/l – 221.72 mg/l – 2.6921 mg/l – 1.136 mg/l – 0.037 mg/l ). Moreover, it gave the lower concentrations (0.84 mg/l – 86.75 mg/l – 0.0081 mg/l – 0.0133 mg/l – 0.017 mg/l ). The results demonstrate that the exchange of water and sediments helps limit nutrient cycling and reduce the risk of eutrophication in the study area. The findings of this study provide essential baseline data for ongoing monitoring and appropriate management of nutrient enrichment. Identifying nutrient enrichment status in the waters of the Shatt Al-Arab and the northern Arabian Gulf is expected to aid in protecting ecosystem health and the efficient use of water resources for future strategies.